Some Geometrical Calculations for the Spherical Indicatrices of Involutes of a Timelike Curve in Minkowski 3-Space (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we introduce the spherical indicatrices of involutes of a given timelike curve. Then we give some important relationships between arc lengths and geodesic curvatures of the base curve and its involutes on E31,S21 ,H20 . Additionally, some important results concerning these curves are given.